PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA INTERAKTIF BERBASIS KOMPUTER PADA TOPIK BILANGAN BULAT UNTUK SISWA SD PENDIDIKAN MATEMATIKA FKIP UNRI - Jalinus Jalinus; Jesi Alexander Alim (Tunjuk Ajar: Jurnal Penelitian Ilmu Pendidikan, 2018)
Problems faced today both teachers and students in learning mathematics, among others: the lack of variation of teaching methods teachers in the delivery of materials for students, still low student motivation in learning, the lack of media used by teachers in delivering the material. From the facts obtained, then the research team tried to provide solutions of these problems is the right to do the development of teaching materials / interactive media-based computer. Computer technology can be utilized to design interactive teaching materials/media. This computer-based interactive teaching material presents digital material with animations that are more interesting and fun for counting times, for, plus and less. The form of research conducted is Research and Development. This development is done based on elementary students’ characteristics. So they are quicker to grasp the lessons of concrete matters combined with animation. Validation results from expert show that computer-based interactive mathematical teaching materials on integer material have been valid (teaching material has been in accordance with the forbidden). The results of trials conducted in the fourth class of elementary school showed that computer-based interactive learning materials on digital material have been practical. It can be concluded that the teaching materials effective in generating student learning activities and can make students learn independent and fun.